Theories of psychotherapy and counseling concepts and cases - Sharf, Richard S. (Brook/Cole Pub., 1996)
Case examples and therapist-client dialogues show how each of 12 major theories can be applied to common psychological disorders (such as depression, anxiety, and borderline disorders) or to modes of treatment (such as individual, couples, families, and groups). Each theory chapter follows a similar organizational scheme, covering goals, assessment, the therapeutic relationship, techniques, research, current trends, time-limited approaches, and multicultural and gender issues. Comparison, critique, and theoretical integration are provided in the final chapter.